STUDENTS-TRANSLATORS PROFESSIONAL COMPETENCE DEVELOPMENT: THEORETICAL OUTLINE - Vysotskaya, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper deals with the problems of students-translators professional competence development in the framework of terminological expertise acquisition. Terminological work is stated to be one of the key means of translation competence development. The emphasis is made on theoretical aspect of the matter. The clarification of basic concepts – competence, translation competence, and terminological competence – is provided. Translation competence is viewed as a set of several sub-competences, characterizing translator’s social, communicative and properly text-oriented skills. Terminological competence is viewed as the constituent of translation competence. The objectives and the tasks of terminological work for Translation students are stated. Curriculum components resulting in terminological expertise acquisition are analyzed. The system of exercises aimed at terminological competence development is outlined.